Live Birth in Woman With Premature Ovarian Insufficiency Receiving Ovarian Administration of Platelet-Rich Plasma (PRP) in Combination With Gonadotropin: A Case Report - Hsu, Chao-Chin; Hsu, Leonard; Hsu, Isabel; Chiu, Yi-Jen; Dorjee, Sonam (Frontiers in Endocrinology, 2020)
The conception rates among women with premature ovarian insufficiency (POI) remain extremely low. To achieve a successful pregnancy, most of these women have to receive donor oocytes through IVF treatment. Ovarian administration of platelet rich plasma (PRP) has been recently applied to enhance the ovulatory function in women with poor ovarian response. However, no live birth has been reported for this application in patients with POI. In this study, we present a 37-year-old woman with POI who had secondary amenorrhea for six months. The clinical manifestations and evaluation of this women with a diminished ovarian function were undetectable serum level of AMH (<0.02ng/mL) and an elevated serum level of FSH (63.65mIU/mL). Single dose of autologous PRP (extracted from 40 mL of peripheral blood) in combination with gonadotropin (150IU rFSH/75 IU rLH) was directly injected into the stroma of bilateral ovaries via the vaginal sonographic guidance. Following the treatment, this patient received controlled ovarian stimulation and IVF procedure in the successive months. Following embryo culture, three cleavage-stage embryos were transferred, leading to a successful pregnancy, which later resulted in the live birth of twins. The case report provides one example of alternative therapy that allows POI patients to use autologous oocyte in IVF treatment.